Modulation of Maternal Immune System During Pregnancy in the Cow - Oliveira, L. J.; Barreto, R. S. N.; Perecin, F.; Mansouri-Attia, N.; Pereira, F. T. V. [UNESP]; Meirelles, F. V. (Wiley-Blackwell, 2012)
There is a molecular crosstalk between the trophoblast and maternal immune cells of bovine endometrium. The uterine cells are able to secrete cytokine/chemokines to either induce a suppressive environment for establishment of the pregnancy or to recruit immune cells to the endometrium to fight infections. Despite morphological differences between women and cows, mechanisms for immune tolerance during pregnancy seem to be conserved. Mechanisms for uterine immunesuppression in the cow include: reduced expression of major histocompatability proteins by the trophoblast; recruitment of macrophages to the pregnant endometrium; and modulation of immune-related genes in response to the presence of the conceptus. Recently, an eGFP transgenic cloned embryo model developed by our group showed that there is modulation of foetal proteins expressed at the site of syncytium formation, suggesting that foetal cell can regulate not only by the secretion of specific factors such as interferon-tau, but also by regulating their own protein expression to avoid excessive maternal recognition by the local immune system. Furthermore, foetal DNA can be detected in the maternal circulation; this may reflect the occurrence of an invasion of trophoblast cells and/or their fragment beyond the uterine basement membrane in the cow. In fact, the newly description of exosome release by the trophoblast cell suggests that could be a new fashion of maternal-foetal communication at the placental barrier. Additionally, recent global transcriptome studies on bovine endometrium suggested that the immune system is aware, from an immunological point of view, of the presence of the foetus in the cow during early pregnancy.